Les conditions favorisant le développement de la réflexion éthique chez des enseignants de l’ordre collégial - Christiane Gohier; France Jutras; Luc Desautels; Philippe Chaubet (Recherches en Éducation)
This article presents the results of a collaborative research on the development process of ethical reflection in college level teachers in which two groups of teachers participated. The case studies of situations involving ethical questions proposed by the participants are the main modus operandi that they chose in order to generate reflection and discussion on ethical issues. The results presented here come from the analysis of one discussion and of summary sheets filled in by the participants after each meeting and concern the conditions favouring the development of ethical reflection.